Narcissism, extraversion and adolescents’ self-presentation on Facebook - Ong, Eileen Y.L.; Ang, Rebecca P.; Ho, Jim C.M.; Lim, Joylynn C.Y.; Goh, Dion H.; Lee, Chei Sian; Chua, Alton Y.K. (Personality and individual differences, 2011)
Social Networking Sites (e.g. Facebook), which afford self-presentation, are gaining popularity amongst adolescents. This study examined the relationship of narcissism and extraversion on adolescents’ self-presentation in four Facebook profile features (profile picture, status updates, social network size, photo count), as reported by Grade 7–Grade 9 adolescents. After accounting for extraversion, narcissism predicted features presenting self-generated content (profile picture rating, status update frequency), but not features presenting system-generated content (social network size, photo count).